Contact dynamics : method of differential specific forces - Goloshchapov, Nikolay (Oakville, ON, Canada ; Palm Bay, Florida : Apple Academic Press Inc., 2019)
"This new book, Contact Dynamics: Methods of Differential Specific Forces, describes the application of the method of the differential specific forces (MDSF). By using this new method, the solutions to the problems of a dissipative viscoelastic and elastic-plastic contacts between curvilinear surfaces of two solid bodies can be found. The novelty is that the forces of viscosity and the forces of elasticity can be found by an integration of the differential specific forces acting inside an elementary volume of the contact zone. This volume shows that this method allows finding the viscoelastic forces for any theoretical or experimental dependencies between the distance of mutual approach of two curvilinear surfaces and the radiuses of the contact area. Also, the derivation of the integral equations of the viscoelastic forces has been given and the equations for the contact pressure have been obtained. The viscoelastic and elastic-plastic contacts at impact between two spherical bodies have been examined. The equations for work and energy in the phases of compression and restitution and at the rolling shear have been obtained. Approximate solutions for the differential equations of movement (displacement) by using the method of equivalent work have been derived"--
Problems in contact dynamics between solids -- Method of the differential specific forces (MSDF) -- Dynamics of viscoelastic contacts, tribocyclicity, and viscoelastic lubrication -- Method of the differential specific forces in dynamics of elastoplastic contacts -- Definition of the time of fatigue life and dynamic mechanical properties of materials of the contacting surfaces.
OCLC-licensed vendor bibliographic record.
Keywords: Contact mechanics; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; SCIENCE / Physics; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Material Science